"I was able to take part in the chamber as if I was there" – women local councillors, remote meeting attendance, and Covid-19: a positive from the pandemic?. Issue 1 (2nd January 2022) - Hibbs, Leah
ABSTRACT: This article explores research findings regarding the possibilities offered by remote attendance at council meetings as implemented during the coronavirus (Covid-19) pandemic, and reflects upon how this may improve women local councillors' experiences, as well as women's political participation and the accessibility of Welsh local government going forward. Influenced by feminist institutionalist theory, this paper examines how councils' formal organisational norms and practices pre-pandemic privileged presenteeism, and explores participants' perceptions and experiences of the accessibility of local councils, especially for younger women with families and/or in other forms of employment. Presenting data from 19 semi-structured interviews with women local councillors in Wales (UK), both in-person and subsequently online during the pandemic, the paper discusses how remote attendance in local council meetings was considered an enabling shift in formal organisational practices, especially for rural councils. Despite some dissenting opinions and voiced dubiousness (mostly concerning future hybrid implementation), through easing the time costs of being a local councillor, particularly for women balancing a gendered 'triple duty' of the political, personal, and professional, remote meeting attendance is an organisational solution, albeit somewhat forced in implementation, which presents clear means of improving women's political participation and representation in local government.